A guide to SQL - Pratt, Philip J. (Danvers : Boyd & Fraser Publishing Co., 1995)
Intended for readers interested in Structured Query Language, from programmers to end users, this text uses a project-oriented, practical approach to discuss the use of SQL in a variety of environments.
Chapter 1. Introduction -- Chapter 2. Data Definition -- Chapter 3. Single-table Queries -- Chapter 4. Multiple-table Queries -- Chapter 5. Updates -- Chapter 6. Database Administration -- Chapter 7. Embedded SQL -- Chapter 8. SQL2.
Includes bibliographical references and index.
Keywords: SQL (COMPUTER PROGRAM LANGUAGES)